2018
DOI: 10.1161/jaha.118.009378
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Pulse Pressure Variability During Mechanical Thrombectomy in Acute Ischemic Stroke Patients

Abstract: BackgroundStudies on the role of blood pressure (BP) variability specifically during mechanical thrombectomy (MT) are sparse and limited. Moreover, pulse pressure (PP) has not been considered as a potent hemodynamic parameter to describe BP variability during MT. We assessed the impact of PP variability on functional outcome in acute ischemic stroke patients with large vessel occlusion during MT.Methods and ResultsAcute ischemic stroke patients presenting with large vessel occlusion from January 2012 to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…sICH rates were not significantly related to baseline systolic or diastolic blood pressure (93). Systolic, pulse pressure and mean arterial BP variability during EVT seem to be critically associated with functional outcome (91,92,(95)(96)(97)(98), but data are scarce regarding the association of blood pressure variability during EVT and sICH risk. After EVT, and notably after complete reperfusion, blood pressure variability seems associated with increased rates of sICH (99,100).…”
Section: The Issue Of Blood Pressure In Evt-treated Patientsmentioning
confidence: 95%
See 1 more Smart Citation
“…sICH rates were not significantly related to baseline systolic or diastolic blood pressure (93). Systolic, pulse pressure and mean arterial BP variability during EVT seem to be critically associated with functional outcome (91,92,(95)(96)(97)(98), but data are scarce regarding the association of blood pressure variability during EVT and sICH risk. After EVT, and notably after complete reperfusion, blood pressure variability seems associated with increased rates of sICH (99,100).…”
Section: The Issue Of Blood Pressure In Evt-treated Patientsmentioning
confidence: 95%
“…Numerous studies have recently highlighted the impact of systolic blood pressure in the early phase of AIS treated by EVT (90)(91)(92)(93). The MRCLEAN investigators have found higher systolic BP before EVT associated with increased probability of sICH (94).…”
Section: The Issue Of Blood Pressure In Evt-treated Patientsmentioning
confidence: 99%
“…However, this threshold comes from exclusion criteria of intravenous thrombolysis trials and randomized controlled trials are still lacking to substantiate this position in the setting of LVO. Indeed, decreases in BP below certain thresholds before recanalization (ie, mean arterial pressure (MAP) <70 or 85 mmHg before reperfusion,13–15systolic blood pressure (SBP) <140 mmHg),16 reductions in BP of different magnitudes (≥10% or 40% MAP drop from baseline14 17) and BP variability18 19 have all been associated with worse functional outcomes 15. However, it still remains unclear whether the relationship between the duration of arterial hypotension during MT and the functional outcome is linear and if this relationship is the same under GA and CS.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Lowhagen Henden et al, a mean BP (MBP) fall of > 40% from the baseline was an independent predictor of an unfavorable neurological outcome, in addition to well-established risk factors such as a high baseline NIH Stroke Scale (NIHSS) or a lack of successful recanalization [80]. The results have been confirmed by more recent studies [81,82].…”
Section: Mechanical Thrombectomymentioning
confidence: 84%